Intranasal dexmedetomidine reduces pain scores in preterm infants during retinopathy of prematurity screening - Ozkan Zarif, Nurten; Arayici, Sema; Celik, Kiymet; Kihtir, Zeynep; Ongun, Hakan (Frontiers in Pediatrics, 2024)
Background: This study aimed to investigate the effectiveness of intranasal dexmedetomidine in reducing pain scores during retinopathy of prematurity (ROP) screening examinations in preterm infants.Methods: Infants born at ≤32 weeks of gestational age, undergoing routine ROP examinations in the neonatal intensive care unit, were included in the study and divided into two groups: the standard protocol group (n=43) and the dexmedetomidine group (n=56), over a 1-year period. Both groups received standard procedural preparation including swaddling, oral dextrose, and topical anesthesia with proparacaine. The dexmedetomidine group additionally received intranasal dexmedetomidine at a dose of 1 mcg/kg before the procedure. Pain scores (PIPP score), heart rate, respiratory rate, blood pressure, and oxygen saturation were compared at baseline, 1minute, and 5-minutes during the procedure.Results: There were no significant differences between the groups regarding descriptive and pre-procedure characteristics. In the dexmedetomidine group, the median (25-75p) PIPP score, heart rate, systolic blood pressure and mean (±SD) respiratory rate measured at the 1st minute of the procedure were significantly lower than those in the standard group [PIPP score 10 (8-13) vs 14 (10-16), p<0.001; heart rate 165 (153-176) beats/minute vs 182 (17-190) beats/minute, p<0.001; respiratory rate 60 (±7) breaths/minute vs 65(±9) breaths/minute, p=0.002; systolic blood pressure 78 (70-92) mmHg vs 87 (78-96) mmHg, p=0.024; respectively] whereas the saturation value was significantly higher (88% (81-95) vs 84% (70-92), p=0.036; respectively). By the 5th minute of the procedure, the median (25-75p) PIPP score [4 (2-6) vs 6 (4-10), p<0.001], heart rate [148 (143-166) beats/minute vs 162 (152-180) beats/minute, p=0.001] and respiratory rate [56 (54-58) breaths/minute vs 58 (54-62) breaths/minute, p=0.034] were significantly lower, and the saturation level was significantly higher [96% (94-97) vs 93% (91-96), p=0.003] in the dexmedetomidine group. Additionally, the frequency of adverse effects was significantly lower in the dexmedetomidine group compared to the standard protocol group (11% vs. 47%, p=0.001).Administering intranasal dexmedetomidine before ROP screening examinations was associated with a decrease in pain scores among preterm infants. This suggests its potential as an effective and well-tolerated method for pain management during ROP screenings.